2020
DOI: 10.3390/ijerph18010011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Health Loss from Kashin-Beck Disease and Its Relationship with Environmental Selenium in Qamdo District of Tibet, China

Abstract: Kashin-Beck Disease (KBD) is one of major endemic diseases in China. In this study, we estimated the health loss from KBD in Qamdo district of Tibet using the years lived with disability (YLD) metric and investigated the influence of environmental selenium (Se) on it by multiple regression model. The results showed that YLD rates produced a different ranking of health loss of KBD from that produced by prevalence rates between Basu and Luolong County, with higher health loss from KBD (43.61 YLD/1000) but lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…This study also showed significant deficiencies in oral intake of Se (Table S6). These results demonstrate that KBD patients are concentrated in the southwest of Loulong County, which is exceedingly similar to the distribution pattern of non-carcinogenic health risks of insufficient Se intake, and this finding is consistent with the relationship between the incidence of KBD and biogeochemical Se-deficiency [3,5]. In addition, according to the preliminary analysis of the risk factors of KBD in Qamdo City and Longzi County by our previous research, the etiology and pathogenesis of KBD are mainly related to the endemic deficiency of some ETEs in local diet [2,6].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This study also showed significant deficiencies in oral intake of Se (Table S6). These results demonstrate that KBD patients are concentrated in the southwest of Loulong County, which is exceedingly similar to the distribution pattern of non-carcinogenic health risks of insufficient Se intake, and this finding is consistent with the relationship between the incidence of KBD and biogeochemical Se-deficiency [3,5]. In addition, according to the preliminary analysis of the risk factors of KBD in Qamdo City and Longzi County by our previous research, the etiology and pathogenesis of KBD are mainly related to the endemic deficiency of some ETEs in local diet [2,6].…”
Section: Discussionsupporting
confidence: 73%
“…Kashin-Beck Disease (KBD) is a chronic, degenerative, endemic osteochondropathy involving growth cartilage and plates [1,2]. KBD has essentially controlled in China at present through a series of measures such as rural drinking water safety project, grain replacement, and relocation during the 12th and 13th Five-Year Plans period, however, Qamdo City is the most serious and active area of KBD currently [3][4][5][6]. Although a number of studies have been conducted on the etiology of KBD, the most studied and best established KBD etiological theory by researchers have increasingly tended toward concluding that endemic deficiency of trace elements in local diets [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be several influencing factors according to the literature. Evaporation plays a certain role in the increase in ions in lake water (Wang et al 2020a ). The lakes in the TP are mainly endorheic; thus, fluoride is concentrated in the lakes as water evaporates.…”
Section: Resultsmentioning
confidence: 99%
“…KBD seriously affect physical, psychological health and social aspects of paients, and causes serious economic burden to their families and society [10] . In China, although the prevalence of KBD has reached the level of elimination or control in the majority of affected areas, the loss of health life due to KBD should not be ignored [11] . The pain and limited range of joint were the independent risk factors of daily living and working function [12] .…”
Section: Introductionmentioning
confidence: 99%